2007
DOI: 10.1111/j.1745-4549.2007.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Idli Batter During Its Fermentation Time

Abstract: Idli is a traditional fermented rice and black gram‐based breakfast food of South India. Idli batter was prepared from soaking polished parboiled rice and decorticated black gram for 4 h at 30 ± 1C in water. The soaked mass was ground to 0.5‐ to 0.7‐mm particle size batter using wet grinder with adequate amount of water. The blend ratios of 2:1, 3:1 and 4:1 (v/v) batter were allowed for fermentation (0, 6, 12, 18 and 24 h) adding 2% of salt. The idli batter parameters viz. bulk density, pH, percent total acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 5 publications
2
27
0
Order By: Relevance
“…Ghosh and Chattopadhyay (2011) reported that increase in blend ratio significantly increased the batter density. Balasubramanian and Viswanathan (2007) reported similar bulk density between 0.94 and 0.59 g cm -3 in idli batter with different ratios of rice and black gram [2:1, 3:1 and 4:1 (v/v)]. The blend ratios didn't affect the bulk density whereas it decreased with increase in fermentation time.…”
Section: Bulk Density and Viscositymentioning
confidence: 83%
See 1 more Smart Citation
“…Ghosh and Chattopadhyay (2011) reported that increase in blend ratio significantly increased the batter density. Balasubramanian and Viswanathan (2007) reported similar bulk density between 0.94 and 0.59 g cm -3 in idli batter with different ratios of rice and black gram [2:1, 3:1 and 4:1 (v/v)]. The blend ratios didn't affect the bulk density whereas it decreased with increase in fermentation time.…”
Section: Bulk Density and Viscositymentioning
confidence: 83%
“…In case of curry leaves batter the pH 4.32 ± 0.02 (control batter, 16 h) was not obtained even after 24 h of fermentation. Balasubramanian and Viswanathan (2007) who studied idli batter from polished parboiled rice and decorticated black gram blend in a ratio of 2:1, 3:1 and 4:1 (v/v) reported pH and titratable acidity in the range of 5.9-4.1 and 0.443-0.910 %, respectively. Annan et al (2005) reported that the pH of the control batter and soybean batter was almost the same but the acidity was found to be significantly higher in the fortified batter.…”
Section: Results and Discussion Ph And Titratable Aciditymentioning
confidence: 99%
“…The black gram was ground to a fine, smooth paste, while the rice was ground coarsely. Both the batters were then incorporated together in a stainless steel container, 2% (weight/total weight of raw material) salt was added (Balasubramanian and Viswanathan, 2007) and mixed properly. Then the batter was allowed to ferment naturally for 18 hours at overnight room temperature ranging from 26 to 30°C (Murthy and Rao, 1997).…”
Section: Materials and Methods Batter Preparation And Fermentationmentioning
confidence: 99%
“…Basically maize is a hardy crop compared to rice; hence more force was needed to pierce the maize dhokla compared to rice. The springiness value indicated the soft spongy texture of the cooked product, which in turn depends on the quantity of dhal used for preparation (Balasubramanian & Viswanathan, ). The springiness values marginally varied in our product indicating that the softness of dhokla was not significantly different with 2:1 and 3:1 ratios.…”
Section: Resultsmentioning
confidence: 99%